SOCIAL-ECONOMIC FACTORS EFFECTING THE DIVERSITY OF DIETARY CONSUMPTION IN THE SELF SUFFICIENT DIETARY VILLAGE OF KUBU RAYA DISTRICT - ,, Surachman; Kusrini, Novira; Suyatno, Adi (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2013)
The research was conducted in Jeruju Besar village in the district of Kubu Raya and Sungai Bulan village in Sungai Raya District. These two locations were chosen because of its location within program The DEMAPAN (Self Sufficient Dietary Village). The purpose of this research was : (1) to analyze the quality of food consumption in the Desirable Dietary Pattern/DDP communities, Kubu Raya District (DDP score). (2) to analyze the relationship between socio-economic aspects and the diversity of food consumption in the DEMAPAN village in Kubu Raya district. The research was carried out for 6 months, in which the data collection finished for 5 weeks, i.e. from January to June 2013. Population of this research is the head of the family who live in the Village of Sungai Bulan Sungai Raya District, the locations of DEMAPAN program in 2010, and also in the village of Jeruju Besar, Sungai Kakap District by 2011. The sample selection was based on Randomize Simplified Sampling method, in which the sample were randomly selected. The research variables were socio-economic factors (income, education, and family size), Score DDP (Desirable Dietary Pattern). The results showed that the DDP score of 68.52 in the research area is still low compared to West Kalimantan DDP score of 71.79 and score of 100 DDP ideally. DDP score Jeruju Besar Village were not significantly different than the score DDP in Sungai Bulan Village. Factors effecting the DDP Score in Jeruju Besar were income, education, and number of dependants. While at Sungai Bula Village they were family income and number of dependants. So, the factor of income level, education, and number of dependants were key determination of the level of food diversity in the commuity. Keywords : Social-economic, Food Consumption Diversity, Self Sufficient Dietary Village